An analysis and comparison of multinational officers of the watch in the global maritime labor market. Issue 6 (18th August 2019) - Kartal, Şaban Emre; Uğurlu, Özkan; Kaptan, Mehmet; Arslanoğlu, Yasin; Wang, Jin; Loughney, Sean
ABSTRACT: Officer of the watch (OOW) is an important part of the maritime labor market. For many years, countries have been improving their development of OOWs for the maritime market, in terms of both quantity and quality. As the supply of qualified OOWs for maritime transportation is such an important issue, shipping companies recruit multinational OOWs for both economic and socio-cultural reasons. This study aims to identify the qualifications of an ideal officer that holds office on commercial ships, and to make a comparison among Filipino, Chinese, Indian, Eastern European and Turkish OOWs. The research takes into account expert opinions of a number of shipping companies that employ multinational seafarers. A Fuzzy Analytic Hierarchy Process (FAHP) technique is applied in this study to assist in the comparison of officers. A number of main and sub-criteria are outlined to determine both positive and negative aspects of OOWs from the selected countries for decision making purposes. This study allows maritime countries to evaluate their maritime education and training policies for selection and assessment of OOWs.